Heterogeneity of meningeal B cells reveals a lymphopoietic niche at the CNS borders - Brioschi, Simone; Wang, Wei-Le; Peng, Vincent; Wang, Meng; Shchukina, Irina; Greenberg, Zev J.; Bando, Jennifer K.; Jaeger, Natalia; Czepielewski, Rafael S.; Swain, Amanda; Mogilenko, Denis A.; Beatty, Wandy L.; et al. (Science (American Association for the Advancement of Science), 2021)
The meninges comprise three membranes that surround and protect the central nervous system (CNS). Recent studies have noted the existence of myeloid cells resident there, but little is known about their ontogeny and function, and whether other meningeal immune cell populations have important roles remains unclear (see the Perspective by Nguyen and Kubes). Cugurra et al. found in mice that a large proportion of continuously replenished myeloid cells in the dura mater are not blood derived, but rather transit from cranial bone marrow through specialized channels. In models of CNS injury and neuroinflammation, the authors demonstrated that these myeloid cells have an immunoregulatory phenotype compared with their more inflammatory blood-derived counterparts. Similarly, Brioschi et al. show that the meninges host B cells that are also derived from skull bone marrow, mature locally, and likely acquire a tolerogenic phenotype. They further found that the brains of aging mice are infiltrated by a second population of age-associated B cells, which come from the periphery and may differentiate into autoantibody-secreting plasma cells after encountering CNS antigens. Together, these two studies may inform future treatment of neurological diseases. Science , abf7844, abf9277, this issue p. eabf7844 , p. eabf9277 ; see also abj8183, p. 396 Bone marrow niches adjacent to the brain and spinal cord supply B cells and myeloid cells to the meninges and central nervous system. The meninges contain adaptive immune cells that provide immunosurveillance of the central nervous system (CNS). These cells are thought to derive from the systemic circulation. Through single-cell analyses, confocal imaging, bone marrow chimeras, and parabiosis experiments, we show that meningeal B cells derive locally from the calvaria, which harbors a bone marrow niche for hematopoiesis. B cells reach the meninges from the calvaria through specialized vascular connections. This calvarial–meningeal path of B cell development may provide the CNS with a constant supply of B cells educated by CNS antigens. Conversely, we show that a subset of antigen-experienced B cells that populate the meninges in aging mice are blood-borne. These results identify a private source for meningeal B cells, which may help maintain immune privilege within the CNS.